Pembatasan Kepemilikan Asing Pada Perseroan Terbatas: Apakah Pembatasan Nilai Nominal Saham Saja Sudah Cukup? - Iskandar, Randyaz (Syntax Corporation, 2025)
This study analyses the current regime of ownership restrictions for foreign investment that are applicable in Indonesia with the goal to assess the level of effectiveness of such restrictions against the ever-evolving trend and form of control of companies by shareholders. The result demonstrates that the current restrictions still have imperfections and room-for-improvements that may cause deviation from the original purpose/rationale behind the existence of such restrictions, which was intended to protect national interest of Indonesia as host state and maintain, to certain extent, the ultimate control of the business entities in those sectors which are deemed sensitive by the Government.